2010
DOI: 10.1186/1471-213x-10-73
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Irs2 causes reduced kidney size in mice: role for inhibition of GSK3β?

Abstract: BackgroundMale Irs2-/- mice develop fatal type 2 diabetes at 13-14 weeks. Defects in neuronal proliferation, pituitary development and photoreceptor cell survival manifest in Irs2-/- mice. We identify retarded renal growth in male and female Irs2-/- mice, independent of diabetes.ResultsKidney size and kidney:body weight ratio were reduced by approximately 20% in Irs2-/- mice at postnatal day 5 and was maintained in maturity. Reduced glomerular number but similar glomerular density was detected in Irs2-/- kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…2A). Interestingly, this global reduction of organ size without obvious effects on structural organization has also been reported in the brain and kidney: Irs2 -deficient mice are born with a 35% reduction of brain size [44] and kidney size is reduced by 20% at P5 [45]. Although the brain and kidney are noticeably smaller in Irs2 -deficient mice, all areas are present but reduced proportionally.…”
Section: Discussionsupporting
confidence: 52%
“…2A). Interestingly, this global reduction of organ size without obvious effects on structural organization has also been reported in the brain and kidney: Irs2 -deficient mice are born with a 35% reduction of brain size [44] and kidney size is reduced by 20% at P5 [45]. Although the brain and kidney are noticeably smaller in Irs2 -deficient mice, all areas are present but reduced proportionally.…”
Section: Discussionsupporting
confidence: 52%
“…Previous data from our laboratory showed that IRS2 mRNA was present in murine kidney at higher levels than in metabolic tissues such as liver . In contrast, IRS1 mRNA levels were similar in mouse liver and kidney, but were modestly up‐regulated in Irs2 −/− kidney extracts (data not shown).…”
Section: Resultsmentioning
confidence: 68%
“…Detection of IRS2 protein in mouse kidney extracts was difficult using available antibodies, and required immunoprecipitation to enrich for IRS2 . Immunohistochemistry using available antibodies did not identify specific IRS2 staining in discrete mouse kidney regions or cell types (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the kidney, IRS2 plays a major role in insulin stimulation of renal proximal tubular transport and Akt phosphorylation in vitro [19]. A recent study identified a novel role for IRS2 in renal development and in the regulation of Akt signalling in the kidney [20]. FoxO3a, a member of the Forkhead family of transcription factors, has been identified as a major effector of TGF‐β1 [21].…”
Section: Introductionmentioning
confidence: 99%